FAMILIAL MEDITERRANEAN FEVER AND HYPERCOAGULABILITY - Oshrat E. Tayer-Shifman; Eldad Ben-Chetrit (Mediterranean Journal of Hematology and Infectious Diseases)
Familial Mediterranean fever (FMF) is an autosomal recessive hereditary disease which is characterized by recurrent attacks of fever and peritonitis, pleuritis, arthritis, or erysipelas-like skin disease. As such, FMF is a prototype of autoinflammatory diseases where genetic changes lead to acute inflammatory episodes. Systemic inflammation – in general - may increase procoagulant factors, and decrease natural anticoagulants and fibrinolytic activity. Therefore, it is anticipated to see more thrombotic events among FMF patients compared with healthy subjects. However, reviewing the current available literature and based upon our personal experience, thrombotic events related purely to FMF are very rare. Possible explanation for this discrepancy is that along with the procoagulant activity during FMF acute attacks, anticoagulant and fibrinolytic changes are also taking place. Furthermore, it may well be that during the acute attack of FMF the procoagulant factors are consumed or used for the purpose of inflammation so that nothing is left for their role in the coagulation pathway. Colchicine may also play a role in reducing inflammation thereby decreasing hypercoagulabilty